Tradução e adaptação cultural da Pediatric Eosinophilic Esophagitis Symptom Score (PEESS v2.0) - Santos, Maria Fernanda Oliveira (2017)
Introduction: Eosinophilic Esophagitis (EEo) is a clinical-pathological entity mediated by immune and antigenic mechanisms with non-specific symptoms, especially in infants and pre-school children. It represents an important cause of high gastrointestinal tract morbidity, with a significant increase in its incidence and prevalence in the last decades. Instruments that assess EEo severity have been developed to support diagnosis and treatment of this disease. Objectives: To translate and culturally adapt the Pediatric Eosinophilic Esophagitis Symptom Score (PEESS version2.0), an instrument used to assess pediatric eosinophilic esophagitis symptoms through patients’ and/or parents’ report. Methods: The PEESS was translated through the following stages: initial translation, backtranslation and consensus of independent reviewers through the Delphi technique. We applied the pre-final version of the PEESS to five eight-to-18-year-old patients and to ten parents of two-to-18-year-old patients from a outpatient Pediatric Gastroenterology service (pre-test). Results: We did not observe translations of difficult consensus or grammar inconsistencies during the translation stages. During pre-testing, we identified difficulties in comprehension of some unconventional terms, e.g., “nausea”. Adverbs of frequency, such as “almost never” were also identified as of difficult understanding by patients and parents. Such difficulties may be inherent to the pediatric age group. Eight-year-old or older children should be considered suitable for self-reporting their own symptoms. Conclusions: We have produced a Brazilian version of the Pediatric Eosinophilic Esophagitis Symptom Score (PEESS), which is adapted to the Brazilian culture. This version may be introduced as a clinical and research instrument for the assessement of patients with esophagic disease symptoms. The PEESS represents a breakthrough in the evaluation of symptoms of the pediatric eosinophilic esophagitis, since it reinforces the importance of self-report of patients who experience this disease.